How gender disparities drive imbalances in health care leadership - Hoss MAK; Bobrowski P; McDonagh KJ; Paris NM (Dove Medical Press, 2011)
Mary Ann Keogh Hoss1, Paula Bobrowski2, Kathryn J McDonagh3, Nancy M Paris41Health Services Administration, Eastern Washington University, College of Business and Public Administration, Spokane, WA, USA; 2College of Liberal Arts, Auburn University, Auburn, AL, USA; 3Executive Relations, Hospira Inc, Lake Forest, IL, USA; 4Georgia Center for Oncology Research and Education, Atlanta, GA, USAAbstract: Low female representation in US hospital chief executive officer positions has persisted for decades. This article addresses gender disparity in professional development, the rationale for gender differences, and practical strategies to address this imbalance. The health care workforce consists of 75% women, but according to two recent surveys, ie, a state survey and a survey of the top 100 US hospitals, women hold only about 12% of chief executive officer positions in US hospitals. Significant and dedicated efforts by both individuals and organizations are necessary to rectify this imbalance.Keywords: gender, imbalance, leadership, United States, hospitals